(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
This paper aims at reconstructing the semantic dominant in Polish-language translations of Mikhail Lermontov’s poems. As research material, poems Caucasus (1930) and Dedication to the Poem “The Demon” (1838) were discussed. Their thematic and compositional axis was focused on the Caucasus and the accompanying associative context built by both phonetic and visual elements. The formal and representational layers of poems were analyzed to determine the level of equivalence between Lermontov’s images of the Caucasus Mountains and their re-visualizations in the TT.